DOMICILE COMMUNITY ORIENTATION IN REMOTE VILLAGE (DESCRIPTIVE STUDY IN NEGERI GUGUNG VILLAGE, SUBDISTRICT SIBOLANGIT, DELI SERDANG REGENCY) - DESTI ARIANI (Perspektif Sosiologi, 2012)
ABSTRACT Writing a scription entitled "People in the village Orientation Remote Domicile" descriptive studies in the Negeri Gugung village subdistrict Sibolangit Deli Serdang regency, the background of many groups of society who remain to live in a remote village with state infrastructure is still very limited and access to go out into the village is still very difficult that lives in the remote village can be said is not feasible. The method used in this research is a method of qualitative descriptive approach. The data collection technique is the method of observation, and analysis data. Research refers to the rational choice theory explains that an individual action against the goals and objectives are determined by the value or choice. result studies suggest that people who live in the village Negeri Gugung Affairs by a factor of economic, educational, social, cultural and natural resource factors. Keyword: Domicile orientation, Rural, Remote villages.